2013
DOI: 10.13080/z-a.2013.100.032
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and lignin partitioning in switchgrass biomass (Panicum virgatum L.) as a bioenergy feedstock

Abstract: Approaching switchgrass (Panicum virgatum L.) as a multifunctional energy plant, it is important to comprehensively study the composition and partitioning of organic substances in the biomass. The character of carbohydrates and lignin concentration variation was assessed in switchgrass biomass cut at two maturity stages (heading and seed filling) in the first and second harvest years. Quality components partitioning in the biomass of aboveground plant parts was examined in leaves, stems and panicles of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
6
17
2
1
Order By: Relevance
“…Here, holocellulose content in miscanthus corresponded with data recorded for plantations in the temperate climate zone [19,32,33]. Lower holocellulose contents in switchgrass biomass were also observed earlier [34,35]. Regarding cellulose, the main holocellulose component, the determined contents for M. × giganteus, M. sacchariflorus and M. sinensis (Table 2), also fell within the ranges for these species cultivated in other temperate regions [19,32,33,36,37].…”
Section: Composition Of Miscanthus and Switchgrass Biomass As A Feedssupporting
confidence: 81%
“…Here, holocellulose content in miscanthus corresponded with data recorded for plantations in the temperate climate zone [19,32,33]. Lower holocellulose contents in switchgrass biomass were also observed earlier [34,35]. Regarding cellulose, the main holocellulose component, the determined contents for M. × giganteus, M. sacchariflorus and M. sinensis (Table 2), also fell within the ranges for these species cultivated in other temperate regions [19,32,33,36,37].…”
Section: Composition Of Miscanthus and Switchgrass Biomass As A Feedssupporting
confidence: 81%
“…Switchgrass has a disadvantage in yielding capability during the first harvest years due to the allocation of a large amount of energy for developing a strong root system (McLaughlin, Kszos, 2005). A similar tendency was obtained in Northwest and Southern Europe (Elbersen, 2001;Butkutė et al, 2013). However, this trend had no relations with chlorophyll content dynamics presented in this paper.…”
Section: Discussionsupporting
confidence: 69%
“…Switchgrass investigations under cool temperate climate conditions are scarce. Initial research on switchgrass showed promising results of this grass as solid biofuel and biogas stock under Lithuanian temperate climate conditions (Butkutė et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the cassava stem, other lignocellulose residues were also reported ( Table 3). The cellulose content from the cassava stem was compared to other reported cellulose content such as 44% for Acacia mangium and 42% for Acacia hybrid (Boondaeng et al, 2015), 26-43% for bamboo (Sánchez, 2009), 42-45% for corn cob (Kuhad and Singh, 1993;Prasad et al, 2007;Liu et al, 2010), 20-25% for hardwood (McKendry, 2002), 43% for the empty fruit bunch of oil palm (Garcia-Nunez et al, 2016), 28-36% for rice straw (Chen et al, 2008;Saini et al, 2015), 27-30% for softwood (McKendry, 2002), 42-48% for sugarcane bagasse (Kuhad and Singh, 1993;Rocha et al, 2015;Saini et al, 2015) and 5-34% for switch grass (Butkute et al, 2013;Saini et al, 2015). These figures indicated that cassava stem has a high potential to be used as a feedstock in bioconversion processes for ethanol fermentation, especially as it can be obtained in large quantities from local growers.…”
Section: Chemical Composition Of Cassava Stem Woodmentioning
confidence: 70%